(untitled) (Encuentros, 2020)
The purpose of this research is to analyze the obligations of States in the field of social rights in the universal human rights system, considering the observations of the Economic and Social Council - Ecosoc. In this way, it confirms the hypothesis related to the fragility of international conditions in the field of social rights, which implies that States have a lesser degree of imperative to comply with them in comparison with the case of civil and political rights. This has generated dynamics that imply less enforceability of social rights given the problems involved in their justiciability, strengthening the margin of appreciation by the States.